AT THE BEGINNING OF THE BIOSTRATIGRAPHY (TO THE 250TH ANNIVERSARY OF THE BIRTHDAY OF WILLIAM SMITH) - I. A. Shcheglov; F. F. Akhunov; R. U. Eremenko; V. N. Komarov (Известия высших учебных заведений: Геология и разведка, 2018)
The main side of the W. Smith’s work — geological mapping — has been shown to be expressed in the series of maps, created by him, and first of all in the «Map of layers of England and Wales». The layers represented for Smith an object for mapping. His stratigraphic tables constitute the lists of stratons, systemized in the order of their bedding and origin. W. Smith discovered a general sequence of 34 layers ofEnglandandWales, in more detailes separated the deposits, substracted later in the Jurassic system. Fossils were considered by W. Smith as specific features of layers, being mapped. The very combination of the characteristics of talented geologist — map-maker und collector of fossils — allowed making the famous conclusion that every layer contained the fossils, typical exactly for it. W. Smith showed the specifics and continuity of paleontological characteristics of different layers, predefined the oportunity of their recognition and identification and designed the base for the development of biostratigraphic method and historical geology in a whole. The short biographic data for Smith has been given.